2018
DOI: 10.1111/ejn.14251
|View full text |Cite
|
Sign up to set email alerts
|

Opto nongenetics inhibition of neuronal firing

Abstract: Optogenetics is based on the selective expression of exogenous opsins by neurons allowing experimental control of their electrical activity using visible light. The interpretation of the results of optogenetic experiments is based on the assumption that light stimulation selectively acts on those neurons expressing the exogenous opsins without perturbing the activity of naive ones. Here, we report that light stimulation, of wavelengths and power in the range of those normally used in optogenetic experiments, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 44 publications
(74 reference statements)
6
40
2
Order By: Relevance
“…Heycke et al 77 ), prespecified sequences of studies (e.g. Ait Ouares et al 78 ) or incremental registrations after Stage 2 acceptance.…”
Section: Rrs Are Only For "Single Shot" Studiesmentioning
confidence: 99%
“…Heycke et al 77 ), prespecified sequences of studies (e.g. Ait Ouares et al 78 ) or incremental registrations after Stage 2 acceptance.…”
Section: Rrs Are Only For "Single Shot" Studiesmentioning
confidence: 99%
“…How does MIR light activate neurons without opsins? This activation was unlikely due to general heating, because previous studies have shown that heating (up to 2℃) by VIS light at a comparable power level (e.g., 15 mW in their studies versus the 9 mW of MIR in our study) either does not change or even suppresses neuronal activities through activation of an inwardly rectifying potassium conductance 17,18 .…”
Section: Mainmentioning
confidence: 48%
“…A recent study reported that gene transcription and neuronal firing rates were impaired following exposure to blue light 9,13 . However, the underlying mechanism was thought to be due to the heat that was produced by light exposure.…”
Section: Discussionmentioning
confidence: 99%